FORMATION OF LEGAL CULTURE OF THE OFFICERS OF THE NATIONAL POLICE OF UKRAINE - O. O. Diakova (Bulletin of Kharkiv National University of Internal Affairs, 2018)
The issue of interpretation of the content of legal culture in general and legal awareness in particular has been studied. Particular attention is paid to legal awareness and legal culture of police officers in Ukraine, to the conditions of formation of legal culture within difficult for Ukraine period of the formation of a democratic European country, because in most countries of the world the key factor in the police training is to form certain personal qualities. A comparative analysis of the formation process of legal culture of police officers in Ukraine and during the Soviet times has been conducted.Attention is paid to conditions causing the direct impact on the officers of the National Police of Ukraine in the course of professional activities, as factors in the formation of legal awareness.It is emphasized that raising the level of legal culture of police officers will contribute to the formation of legal country, as the subject of legal enforcement itself will declare by own example the importance of this principle and the formation of a democratic state, where human rights and freedoms are respected and protected.The propositions to raise the level of legal awareness and legal culture of Ukrainian police officers have been provided.